User Oriented Approach in Information Communication Technology Research - Zuzana Juchova Juroskova; Boris Bucko (Communications - Scientific letters of the University of Zilina, 2017)
User-oriented approach is changing the way of information systems development and affects the processes, methodologies and paradigms proposed by software architects and developers. In line with that trend we carried out two separate studies where the users were involved in the whole process of the development. The first study used experiment, data mining and text mining and was focused on identifying opportunities for obtaining values of bibliographic elements to digitize objects in order to maximize the quality and quantity of delivering meta-data value elements of physical objects Slovak library database from a user‘s perspective. The second study used experiment and was focused on the design of the architectural framework for information system solutions for knowledge management in the organization by using the principles of model-driven architecture (MDA) and ontology modeling language within the CIM (Computer Independent Model) and PIM (Platform Independent Model) levels.